Quality of the charcoal obtained from the Cecropia glaziovii Sneth. species produced in the family-based agriculture in Santa Catarina - Carvalho, Adriel Furtado de; Brand, Martha Andreia; Higuchi, Pedro; Silva, Ana Carolina da (Revista de Ciências Agroveterinárias, 2020)
The objective of this work was to assess the quality of the charcoal of the species Cecropia glaziovii, produced in small rural properties, in the municipality of Biguaçu, in the state of Santa Catarina, and in the laboratory and to compare its properties with charcoal from other species. We analyzed charcoal samples from three sources: charcoal samples collected from Cecropia glaziovii kilns Biguaçu, SC (1), charcoal samples produced in these same kilns, but from several different species (2) and samples obtained from the laboratory carbonization of woods from three Cecropia glaziovii trees collected in the same rural properties (3). It was determined the gross calorific value, percentage of volatile, percentage of ash, and fixed carbon. Analyzing the samples of charcoal, the averages for the energy analysis showed that the charcoal from sample 2 presents better characteristics compared to the samples 1 and 3. Sample 2 had a gross calorific value (GCV - 7,281 Kcal/Kg to 7,336 Kcal/Kg), lowest volatiles content (TV - 26.26%), lower ash content (TC - 2.05 to 2.46%) and higher fixed carbon content (66.02%). The average of the properties of Sample 3 was also compared to other species of commercial importance to produce charcoal. The gross calorific value (6,573 Kcal/Kg) and percentage of fixed carbon (61.32%) were respectively lower when compared to other carbon species: Mimosa scabrella (7201.28 Kcal/Kg; 85.40%), Eucalyptus bentamii (8,777 Kcal/Kg; 81.85%), and Eucalyptus grandis (7632 Kcal/Kg; 75-80%). The percentage of volatile (35.00%) and ash (3.68%) were respectively higher than those from other species: Mimosa scabrella (12.70%; 1.90%), Eucalyptus bentamii (17.17%; 0.96%) and Eucalyptus grandis (20-25%; 1.70%). The results indicate that the quality of the Cecropia glaziovii charcoal is lower when comparing to other species. However, its production is recommended due to the abundance of the species in this region.